FLOTATION CONCENTRATION STUDY OF PRINTED CIRCUIT BOARD FROM ELECTRONIC WASTE USING DIESEL OIL AND OLEIC ACID COLLECTORS - Zahira Hidayat, Fairuz
Printed Circuit Board (PCB) is a board for placing electronic components on conductive paths that are connected to each other. The amount of PCB waste increases along with the increase in electronic waste. Total electronic waste production in 2019 in the world was 53.6 million metric tons (Mt) and Asia was in the first place with 24.9 Mt. PCBs contribute 7% of the total weight of electronic waste with a PCB composition consist of 40% metal, 30% plastic, and 30% ceramic. Conventional disposal of PCB waste produces heavy metals which are dangerous for organism and the environment. Therefore, PCB waste recycling is carried out because there are several metals which content is higher than ore. This research uses mixed C type PCBs with a flotation method using a Philips mixer for conditioning and a Denver flotation cell for aeration. A series of two-stage flotation experiments using diesel oil and oleic acid collectors was operated to study the effect of pH and collector dosage on the density of the flotation product. High density indicates a large amount of metal. The influence of feed size fraction on metal content and recovery was also studied. The pH variations ran at 5, 7, and 9 with dosages of 400, 780, and 1200 gpt in size fractions -210 +149, -149 +105, -105 +74, and -74 +38 ?m. Flotations were undertaken at a pulp condition of 15% solids with a mixer stick speed of 1020 rpm and a flotation cell impeller of 1200 rpm. Flotations were held for 10 minutes for conditioning and 5 minutes for aeration. Density testing was carried out on the flotation product of variations in pH and collector dosage, and then X-Ray Fluorescence (XRF) analysis was carried out on the concentrate resulting from flotation variations in size fractions. The initial metal content in the PCB sample was 47.61%. Experiments using diesel oil and oleic acid collectors showed a decreasing trend in metal content and recovery as the finer feed size fraction. The highest metal content and recovery is 78.66% and 52.17%, were obtained from experiments using a diesel oil collector with an amount of 780 gpt at pH 7 for the -210 +149 ?m size fraction. The best experiment for the oleic acid collector was obtained with an amount of 400 gpt at pH 9 and a size fraction of -210 +149 ?m which resulted in metal content and recovery is 57.18% and 23.28%.